Assessment of gonadotropins and testosterone hormone levels in regular Mitragyna speciosa (Korth.) users - Singh, D. (Elsevier Ireland Ltd, 2018)
Ethnopharmacological relevance: Mitragyna speciosa (Korth.) also known as kratom, is a native medicinal plant of Southeast Asia with opioid-like effects. Kratom tea/juice have been traditionally used as a folk remedy and for controlling opiate withdrawal in Malaysia. Long-term opioid use is associated with depletion in testosterone levels. Aim of the study: Since kratom is reported to deform sperm morphology and reduce sperm motility, we aimed to clinically investigate the testosterone levels following long-term kratom tea/juice use in regular kratom users. Methods: A total of 19 regular kratom users were recruited for this cross-sectional study. A full-blood test was conducted including determination of testosterone level, follicle stimulating hormone (FSH) and luteinizing hormone (LH) profile, as well as hematological and biochemical parameters of participants. Results: We found long-term kratom tea/juice consumption with a daily mitragynine dose of 76.23â94.15 mg did not impair testosterone levels, or gonadotrophins, hematological and biochemical parameters in regular kratom users. Conclusion: Regular kratom tea/juice consumption over prolonged periods (>2 years) was not associated with testosterone impairing effects in humans. Â© 2018 Elsevier B.V.